3D Co-culture of hiPSC-Derived Cardiomyocytes With Cardiac Fibroblasts Improves Tissue-Like Features of Cardiac Spheroids - Beauchamp, Philippe; Jackson, Christopher B.; Ozhathil, Lijo Cherian; Agarkova, Irina; Galindo, Cristi L.; Sawyer, Douglas B.; Suter, Thomas M.; Zuppinger, Christian (Frontiers in Molecular Biosciences, 2020)
Purpose: Both cardiomyocytes and cardiac fibroblasts (CF) play essential roles in cardiac development, function, and remodeling. Properties of 3D co-cultures are incompletely understood. Hence, 3D co-culture of cardiomyocytes and CF was characterized, and selected features compared with single-type and 2D culture conditions. Methods: Human cardiomyocytes derived from induced-pluripotent stem cells (hiPSC-CMs) were obtained from Cellular Dynamics or Ncardia, and primary human cardiac fibroblasts from ScienCell. Cardiac spheroids were investigated using cryosections and whole-mount confocal microscopy, video motion analysis, scanning- and transmission-electron microscopy (SEM, TEM), action potential recording, and quantitative PCR (qPCR). Results: Spheroids formed in hanging drops or in non-adhesive wells showed spontaneous contractions for at least one month with frequent media changes. SEM of mechanically opened spheroids revealed a dense inner structure and no signs of blebbing. TEM of co-culture spheroids at one month showed myofibrils, intercalated disc-like structures and mitochondria. Ultrastructural features were comparable to fetal human myocardium. We then assessed immunostained 2D cultures, cryosections of spheroids and whole-mount preparations by confocal microscopy. CF in co-culture spheroids assumed a small size and shape similar to the situation in ventricular tissue. Spheroids made only of CF and cultured for three weeks showed no stress fibers and strongly reduced amounts of alpha smooth muscle actin compared to early spheroids and 2D cultures as shown by confocal microscopy, western blotting and qPCR. The addition of CF to cardiac spheroids did not lead to arrhythmogenic effects as measured by sharp-electrode electrophysiology. Video motion analysis showed a faster spontaneous contraction rate in co-culture spheroids compared to pure hiPSC-CMs, but similar contraction amplitudes and kinetics. Spontaneous contraction rates were not dependent on spheroid size. Applying increasing pacing frequencies resulted in decreasing contraction amplitudes without positive staircase effect. Gene expression analysis of selected cytoskeleton and myofibrillar proteins showed more tissue-like expression patterns in co-culture spheroids than with cardiomyocytes alone or in 2D culture. Conclusion: We demonstrate that the use of 3D co-culture of hiPSC-CMs and CF is superior over 2D culture conditions and more closely mimicking the native state of the myocardium with relevance to drug development as well as for personalized medicine.